2008
DOI: 10.1002/tcr.20154
|View full text |Cite
|
Sign up to set email alerts
|

Wettability control of a solid surface by utilizing photocatalysis

Abstract: This paper describes a strategic approach utilizing a photocatalyst to obtain a solid surface with a high level of sustainable wettability (hydrophilicity or hydrophobicity). We clarified that the substances adsorbed on the surface could be successfully removed by photocatalytic oxidation resulting in sustainable high hydrophilic and high hydrophobic states. In addition to the conventional redox reaction, photoinduced wettability conversion plays an inevitable role in obtaining a superhydrophilic state. Both o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 33 publications
0
18
0
Order By: Relevance
“…Recently, it has been reported that photo-induced hydrophilicity is not only because of photo-oxidation of hydrophobic contaminant layers but also because of structural changes of the TiO 2 surface [45]. However, the F-TiO 2 film in this work was surface fluorinated, which means the surface hydrophobic species of Ti-F cannot be practically removed under UV irradiation.…”
Section: Photo-induced Hydrophilicitymentioning
confidence: 92%
“…Recently, it has been reported that photo-induced hydrophilicity is not only because of photo-oxidation of hydrophobic contaminant layers but also because of structural changes of the TiO 2 surface [45]. However, the F-TiO 2 film in this work was surface fluorinated, which means the surface hydrophobic species of Ti-F cannot be practically removed under UV irradiation.…”
Section: Photo-induced Hydrophilicitymentioning
confidence: 92%
“…These include the reduction of bacterial adhesion11 and the superior cleaning action of the lotus effect (versus water sheeting),12 in addition to providing other superhydrophobic properties such as water proofing and anti‐misting 6. There are limited examples of superhydrophobic photocatalysts in the literature,13–19 however, without exception, these materials either lose their superhydrophobicity upon irradiation with light or do not show photocatalytic breakdown of material. Here we report the formation of a new class of material that is simultaneously both superhydrophobic and photocatalytic.…”
mentioning
confidence: 99%
“…Wettability is highly dependent on the surface morphology 37 and surface energy. 61 Only when the surface energy of solid is greater than the solid-liquid interfacial energy can the saturating process occur spontaneously. 62 A film with a hydrophilic surface has a high surface energy, which is thermodynamically unstable.…”
Section: Photocatalytic Activitymentioning
confidence: 99%